UTILIZATION OF MIND MAPPING LEARNING TO INCREASE THE RESULT OF STUDY GEOGRAPHY STUDENTS GRADE AT SMAN 1 GADINGREJO - Yarmaidi Yarmaidi; I Gede Sugiyanta; Sri Krisna Wisnu Wardhana (Journal Learning Geography, 2020)
This research purpose to know : (1) Knowing the effect of using mind mapping learning to enhancement the result of the study in geography class at senior high school 1 Gadingrejo 2018/2019 Period. The result makes use of experiment method, this research using aggregate technic data random sampling with taking a sample of the basic on all class, each sampling unit as an element of the population which secluded have same opportunity to want to be sample or representation the population, after obtaining 2 class be resolved experiment class and control class, the population in this research 96 students class XI with student sample class XI social 2 as experiment class and XI IPS 1 as control class. The result this study affords of utilization mind mapping learning with indicators as : (1) there impact on mind mapping learning to the result of study geography students class XI social 2 at senior high school 1 Gadingrejo. Penelitian ini bertujuan untuk mengetahui: (1) pengaruh penggunaan model pembelajaran mind mapping terhadap peningkatan hasil belajar siswa pada mata pelajaran geografi di SMA Negeri 1 Gadingrejo Tahun Ajaran 2018/2019. Penelitian ini menggunakan metode eksperimen yaitu penelitian yang dilakukan dengan memberikan perlakuan kepada kelompok eksperimen dan menyediakan kelompok kontrol sebagai pembanding. Penelitian ini adalah penelitian yang menggunakan random sampling dengan pengambilan sampel yang didasarkan pada semua kelas, dengan demikian setiap unit sampling sebagai unsur populasi yang terpencil memiliki peluang yang sama untuk menjadi sampel atau mewakili populasi, setelah diperoleh dua kelas maka ditentukan kelas eksperimen dan kelas kontrol, populasi dalam penelitian ini berjumlah 96 siswa kelas XI dengan sampel siswa kelas XI IPS 2 dan XI IPS1. Hasil penelitian menunjukkan penggunaan model pembelajaran mind mapping dengan indikator sebagai berikut : (1) Terdapat pengaruh pada model pembelajaran mind mapping terhadap hasil belajar geografi siswa kelas XI IPS 2 di SMA Negeri 1 Gadingrejo.